Improvement of Work Skills and Economic Education of Students in Work Classes (Web of Technology: Multidimensional Research Journal, 2023)
Preparing the young generation for economic activity and employment is one of the main tasks of education and training in current general education schools. This task is carried out both in the general educational system and in vocational education classes.